Professional Competence in Vocational School Education: A Qualitative Research on Students' Expectations and Realised Experiences - Demirkol, Murat (Şahin ORUÇ, 2025)
This study aims to examine the expectations, experiences and challenges faced by vocational school students regarding the process of gaining vocational qualifications, with a particular focus on assessing the extent to which the education students receive in vocational schools is in line with the expectations of the labour market. The participants of the study consist of a total of 24 students enrolled in a Vocational School in eastern Turkey in the academic year 2023-2024. A semi-structured interview form was used as a data collection tool and the participants were carefully selected. The data obtained were subjected to content analysis and themes and sub-themes were formed. The findings of the study revealed that applied education is insufficient in vocational colleges and that students prefer more applied courses. The lack of adequate technical infrastructure was identified as an obstacle to their professional development. In addition, it was observed that students stated that the labour market requires extensive practical experience and that the current education system is not equipped to provide this. The importance of internships and field studies in gaining professional competence was emphasised, but it was stated that these areas also have their own shortcomings.

Bu çalışma, meslek okulu öğrencilerinin mesleki yeterlilik kazanma sürecine ilişkin beklentilerini, deneyimlerini ve karşılaştıkları zorlukları incelemeyi ve özellikle öğrencilerin meslek okullarında aldıkları eğitimin işgücü piyasasının beklentileriyle ne ölçüde uyumlu olduğunu değerlendirmeye odaklanmayı amaçlamaktadır. Çalışmanın katılımcıları, 2023-2024 akademik yılında Türkiye'nin doğusundaki bir Meslek Yüksekokuluna kayıtlı toplam 24 öğrenciden oluşmaktadır. Veri toplama aracı olarak yarı yapılandırılmış bir görüşme formu kullanılmış ve katılımcılar titizlikle seçilmiştir. Elde edilen veriler içerik analizine tabi tutularak tema ve alt temalar oluşturulmuştur. Çalışmanın bulguları, meslek yüksekokullarında uygulamalı eğitimin yetersiz olduğunu ve öğrencilerin daha çok uygulamalı dersleri tercih ettiklerini ortaya koymuştur. Yeterli teknik altyapının olmaması, mesleki gelişimlerinin önünde bir engel olarak tanımlanmıştır. Ayrıca, öğrencilerin işgücü piyasasının kapsamlı pratik deneyim gerektirdiğini ve mevcut eğitim sisteminin bunu sağlayacak donanıma sahip olmadığını belirttikleri gözlemlenmiştir. Mesleki yeterlilik kazanmada staj ve saha çalışmalarının önemi vurgulanmış, ancak bu alanların da kendi eksiklikleri olduğu belirtilmiştir.
Meslek Yüksekokulu Eğitiminde Mesleki Yeterlilik: Öğrencilerin Beklentileri ve Gerçekleşen Deneyimleri Üzerine Nitel Bir Araştırma
Keywords: Other Fields of Education (Other); Alan Eğitimleri (Diğer)